Anatomical responses to cytokinins of abscised grapevine shoot apices cultured in vitro - Goussard, P. G. (South African Journal of Enology and Viticulture, 2017)
Responses of excised shoot apices of V. vinifera L. cv. Chenin blanc to different cytokinin treatments were studied at various intervals (days) after the start of in vitro culture, using light and scanning electron microscopy. Results clearly indicated that in vitro produced shoots were of axillary origin. Shoot clusters were produced by the enhanced release of axillary meristems from apical dominance, due to the application of 6-benzylaminopurine (BAP) singly as well as in combination with zeatin riboside (ZR). Axillary meristems on these axillary shoots were subsequently released from apical dominance, thus giving rise to shoot clusters of high densities. Shoot clusters induced by ZR alone were less dense, probably due to an initial delay in elongation of axillary meristems nearest to the main apical meristem of the shoot. However, elongation of axillary meristems lower down the axes proceeded strongly in the presence of ZR. Application of BAP resulted in more pronounced release of axillary meristems from apical dominance than with ZR.